STUDI KORELASIONAL PEMBERDAYAAN ANGGOTA KELOMPOK PETANI KECIL (KPK) DALAM PERSPEKTIF MODERNITAS INDIVIDU, JEJARING KERJA, DAN KEMAMPUAN MANAJERIAL KETUA KPK - Thomas Widodo (Fakultas Pertanian Universitas Borobudur, 2018)
The objecive of this research is to study the relationship between, individual modernity, networking and managerial ability with the empowerment for member of small farmer group. The research was carried out at Bogor District, West Java Province with a sample of 90 selected by multiple stage random sampling. The study finds out that there is positive correlation between: (a) individual modernity and empowerment; (b) networking and empowerment; (c) managerial ability and empowerment. Therefore empowerment for member of small farmer group can be improved by enhancing the individual modernity, networking and managerial ability. Keywords: empowerment, networking, managerial ability